Ketika Ruang Fiskal Gagal Mengurangi Kemiskinan: Filter Tata Kelola dan Kapasitas Fiskal Regional di Provinsi Nusa Tenggara Barat, 2019–2023 - Fathurrahman; Baiq Dewi Lita Andiana; Achmad Suhendri (Jurnal Bina Praja, 2026)
This study examines the mismatch between rising regional fiscal capacity and poverty reduction in West Nusa Tenggara (NTB) Province, 2019–2023. It responds to a puzzle: NTB’s Regional Fiscal Capacity Index rose sharply, especially in 2022–2023, while poverty declined only marginally and fluctuated. The research uses a qualitative approach with an instrumental case study design, supported by quantitative data on fiscal capacity and poverty trends. Data were collected through in-depth interviews, focus group discussions, and document analysis of regional budgets, development plans, performance reports, and official statistics, then analyzed thematically to identify the mechanisms linking fiscal space to social outcomes. Trustworthiness was ensured through source and method triangulation, member checking, audit trails, and cross-source verification. The findings indicate that rising fiscal capacity has not effectively driven poverty reduction because it is constrained by three governance filters: institutional fragmentation across regional government agencies, the dominance of short-term charitable programs, and weaknesses in data systems and beneficiary targeting. Fiscal capacity is therefore a necessary but not sufficient condition for anti-poverty policy success. The study’s contribution lies in developing a fiscal capacity–governance filter–social outcome framework that explains why budgetary capacity fails to convert into welfare gains, extending the fiscal decentralization literature by positioning governance as a mediating mechanism rather than an administrative variable. Policy implications include strengthening the Regional Poverty Reduction Coordination Team, integrating beneficiary databases, adopting outcome-based budgeting, promoting evidence-based evaluation, and improving cross-agency coordination so that fiscal decentralization can work more effectively for poor communities in NTB.